Outbreak of Zika virus infection in Singapore: an epidemiological, entomological, virological, and clinical analysis. Issue 8 (August 2017) - ,; Ho, Zheng Jie Marc; Hapuarachchi, Hapuarachchige Chanditha; Barkham, Timothy; Chow, Angela; Ng, Lee Ching; Lee, Jian Ming Vernon; Leo, Yee Sin; Prem, Kiesha; Lim, Yue Hui Georgina; de Sessions, Paola F; Rabaa, Maia A; et al.
Summary: Background: An outbreak of Zika virus infection was detected in Singapore in August, 2016. We report the first comprehensive analysis of a national response to an outbreak of Zika virus infection in Asia. Methods: In the first phase of the outbreak, patients with suspected Zika virus infection were isolated in two national referral hospitals until their serum tested negative for the virus. Enhanced vector control and community engagement measures were deployed in disease clusters, including stepped-up mosquito larvicide and adulticide use, community participation in source reduction (destruction of mosquito breeding sites), and work with the local media to promote awareness of the outbreak. Clinical and epidemiological data were collected from patients with confirmed Zika virus infection during the first phase. In the second phase, admission into hospitals for isolation was stopped but vector control efforts continued. Mosquitoes were captured from areas with Zika disease clusters to assess which species were present, their breeding numbers, and to test for Zika virus. Mosquito virus strains were compared with human strains through phylogenetic analysis after full genome sequencing. Reproductive numbers and inferred dates of strain diversification were estimated through Bayesian analyses. Findings: From Aug 27 to Nov 30, 2016, 455 cases of Zika virus infection were confirmed in Singapore. Of 163 patients with confirmed Zika virus infection who presented to national referral hospitals during the first phase of the outbreak, Zika virus was detected in the blood samples of 97 (60%) patients and the urine samples of 157 (96%) patients. There were 15 disease clusters, 12 of which had high Aedes aegypti breeding percentages. Captured mosquitoes were pooled into 517 pools for Zika virus screening; nine abdomen pools (2%) were positive for Zika virus, of which seven head and thorax pools were Zika-virus positive. In the phylogenetic analysis, all mosquito sequences clustered within the outbreak lineage. The lineage showed little diversity and was distinct from other Asian lineages. The estimated most recent common ancestor of the outbreak lineage was from May, 2016. With the deployment of vector control and community engagement measures, the estimated reproductive number fell from 3·62 (95% CI 3·48–3·77) for July 31 to Sept 1, 2016, to 1·22 (95% CI 1·19–1·24) 4 weeks later (Sept 1 to Nov 24, 2016). Interpretation: The outbreak shows the ease with which Zika virus can be introduced and spread despite good baseline vector control. Disease surveillance, enhanced vector control, and community awareness and engagement helped to quickly curb further spread of the virus. These intensive measures might be useful for other countries facing the same threat. Funding: National Medical Research Council Singapore, Centre for Infectious Disease Epidemiology and Research, and A*STAR Biomedical Research Council.